Analysis of the Ability Read Short Stories of Elementary School Students in Batanghari Regency - Dewi, Hasana (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2021)
This study examines the reading ability of elementary school students in Batanghari Regency, focusing on their comprehension of short stories. The methodology involved administering reading comprehension tests to a sample of students, followed by analysis using both quantitative and qualitative approaches. Qualitative research aims to understand and explain phenomena in depth through descriptive and interpretive analysis, while quantitative research aims to measure and test relationships between variables using statistical methods and data collection in the form of numbers. The results indicate varying levels of proficiency among the students, with factors such as socio-economic background and access to educational resources playing significant roles. Furthermore, the study highlights the importance of early intervention programs and targeted literacy initiatives in improving reading skills among elementary school students. The novelty of this research lies in its specific focus on a rural area like Batanghari Regency, shedding light on the unique challenges and opportunities faced by students in such contexts. The implications of these findings underscore the need for tailored educational strategies and resource allocation to address literacy disparities and enhance overall learning outcomes in similar regions.